Mystery of king Karfu (The) ([s.l.] : A Trophy Picture Book, 1996)
The great detective Seymour Sleuth and his assistant Muggs journey to Egypt to searh for a missing stone chicken, an important clue to the Lost Treasure of King Karfu.
Keywords: Egypt -- Fiction; Mystery and detective stories